A super biosorbent from dendrimer poly(amidoamine)-grafted cellulose nanofibril aerogels for effective removal of Cr(vi)1. Issue 28 (28th July 2015) - Zhao, Jiangqi; Zhang, Xiaofang; He, Xu; Xiao, Meijie; Zhang, Wei; Lu, Canhui
<x xml:space="preserve">Abstract</x> A dendrimer PAMAM-g-CNF aerogel with unique molecular and microscopic structures demonstrates outstanding performance in Cr(vi) removal.